Investigation of a community cluster of cutaneous Mycobacterium marinum infection, an emerging zoonotic pathogen in aquaculture industry, Haliburton, Kawartha, Pine Ridge District Health Unit, Ontario, Canada, July–August 2015. (24th August 2018) - Sunil, Vidya; Harris, Andrew W.; Sine, Bob; Holt, Anne Marie; Noseworthy, A. Lynn; Sider, Doug; Jamieson, Frances B; White, Shelley; Johnston, Cassandra; Spohn, Olivia
Abstract: In July 2015, a cluster of five suspect cases of clinically diagnosed Mycobacterium marinum ( M. marinum ) skin infections were reported to the Haliburton, Kawartha, Pine Ridge District Health Unit (HKPRDHU), Ontario, Canada, with two additional cases subsequently identified through case finding. All seven cases presented with cutaneous lesions located on the finger, hand and/or elbow regions typical of M. marinum infection. Specimens were collected by skin biopsy for two of the seven cases; both cases tested positive for M. marinum by molecular detection (hsp65 gene amplification and sequencing), and one was confirmed positive for M. marinum by culture. All seven cases reported handling raw shrimp from an aquaculture facility in the Health Unit's jurisdiction. M. marinum is not a reportable disease in Ontario, and there are no known previous reports of a cluster of M. marinum reported in Ontario, Canada. A cluster investigation working group was struck that included representation from various agencies including Public Health Ontario (PHO), Public Health Ontario Laboratories (PHOL), Ontario Ministry of Agriculture and Rural Affairs (OMAFRA) and the two health units involved in case investigations. Several public health and aquaculture farming recommendations were made to mitigate further risks associated with handling of raw shrimp from the facility. Several challenges were faced during the investigation process. The paper discusses these challenges and public health recommendations made in order to mitigate occupational and public health risks related to the hazard identified.